2014
DOI: 10.1128/jb.01238-13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Requirements for Magnesium Transporters in Bacillus subtilis

Abstract: Magnesium is the most abundant divalent metal in cells and is required for many structural and enzymatic functions. For bacteria, at least three families of proteins function as magnesium transporters. In recent years, it has been shown that a subset of these transport proteins is regulated by magnesium-responsive genetic control elements. In this study, we investigated the cellular requirements for magnesium homeostasis in the model microorganism Bacillus subtilis. Putative magnesium transporter genes were mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…Intriguingly, ectopic expression of a proteolytically inactive S288A mutant of YqgP also rescued the phenotype of the parent strain, which was initially surprising and suggested that YqgP may have a role independent of its protease activity. Together, these results reveal that a physiological function of YqgP is the protection from manganese stress by contributing to the degradation of the main magnesium transporter MgtE in B. subtilis (Wakeman et al , ).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Intriguingly, ectopic expression of a proteolytically inactive S288A mutant of YqgP also rescued the phenotype of the parent strain, which was initially surprising and suggested that YqgP may have a role independent of its protease activity. Together, these results reveal that a physiological function of YqgP is the protection from manganese stress by contributing to the degradation of the main magnesium transporter MgtE in B. subtilis (Wakeman et al , ).…”
Section: Resultsmentioning
confidence: 88%
“…The only high‐confidence overlap between the two proteomic datasets was the high‐affinity magnesium transporter MgtE (Fig C and E), promoting it to the highest likelihood candidate substrate. MgtE is the main magnesium transporter in B. subtilis , it is essential for magnesium homeostasis (Wakeman et al , ), and we thus examined the possible functional relationship between YqgP and MgtE.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed studies on MgtE, including crystal structure analyses in Thermus thermophilus, have demonstrated that MgtE is an Mg 2ϩ transporter that plays a central role in Mg 2ϩ homeostasis (52)(53)(54). Recently, it has also been reported that MgtE in B. subtilis, which shows 33% sequence identity with MgtE of T. thermophilus, provides the primary route of magnesium import, although YfjQ, a homologue of the magnesium/cobalt transporter CorA, is also able to import Mg 2ϩ (74). Disruption of yhdP and overexpression of mgtE restored the reduction in the cellular Mg 2؉ content caused by lack of L34.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this notion, the MgtC protein inhibits the F 1 F o ATP synthase thereby reducing ATP levels [5]. Moreover, spontaneous mutations that restored growth to a mutant B. subtilis requiring unusually high Mg 2+ concentrations for growth due to mutations in multiple Mg 2+ transporters mapped to the genes specifying subunits of the F 1 F o ATP synthase [95]. …”
Section: Introductionmentioning
confidence: 99%